A frágil realidade de plástico: um estudo comparativo da imagem Casa de Bonecas em henrik ibsen e katherine mansfield - Rodrigues, Talita Annunciato [UNESP]; Rapucci, Cleide Antonia [UNESP] (Universidade Estadual de Maringa, 2010)
Considering the importance of significations in literary works, this paper proposes a comparative study of the image of the Doll's House in Henrik Ibsen's play ADoll's House (1879), and Katherine Mansfield's short story The Doll's House, published in the book The Dove's Nest (1923), based on the theories of Gaston Bachelard and Jean Baudrillard. In both cases, one notices that the presence of this image indicatesnot only the construction of these works' environment, but also a criticism of the bourgeois model of a perfect and flawless society, as the described image refers to. However, even though this image shares the same idea in both works, it will be explored differentlyin each case, whether through the search of Nora's character in escaping social conformity as in Ibsen, or through the subtle childlike game experienced by the Kelvey sisters, asin Mansfield.
The fragile plastic reality: A comparative study of the image Doll's House in henrik ibsen and katherine mansfield
Keywords: Drama; Literary image; Short story